Studies on Cercospora and allied genera in northern Thailand - Nakashima C. (2014)
New collections of Cercospora species and allied genera from the northern part of Thailand are described and illustrated. These include three new species Passalora haldiniae, Passalora gmeliniicola and Pseudocercospora holmskioldiae as well as 11 records that are species new to Thailand. Furthermore, two species hitherto known from Thailand are briefly discussed.